Types and functions of code-switching in an interview with a bilingual child - Młyński, Rafał; Majewska-Tworek, Anna (Papers in Linguistics, 2024)
The problem of language code-switching (CS) in children is rarely explored by Polish linguists, especially in reference to analyses of recorded and transcribed spontaneous utterances. In two different interviews (speech therapy and biographical), the phenomenon of code-switching was examined in children of early school age for whom Polish is L1 and English is L2. In the literature of the subject, three main types of CS are enumerated: alternation, insertion, and congruent lexicalization (Muysken 1997, 2000). A significant correlation between the sender-receiver relationship and the occurrence of CS is also indicated. Thus, three questions were asked in the present study: what types of CS can be distinguished in the analyzed conversations with bilingual children?; what is the dominant function of CS in the examined utterances?; do the type of interview and the sender- -receiver relationship determined by it influence the occurrence of CS in the examined utterances of the speakers? The analyzed material was dominated by lexical insertions resulting from the functional dominance of L2 in both children. It was noted that the type of sender-receiver relationship affects the use of CS. In addition, both interviews are conducive to the occurrence of CS, and thus to the continuation of verbal interaction.